Hyphenated dispersive solid‐ and liquid‐phase microextraction technique based on a hydrophobic deep eutectic solvent: application for trace analysis of pesticides in fruit juices. (17th February 2020) - Sereshti, Hassan; Jamshidi, Fatemeh; Nouri, Nina; Nodeh, Hamid Rashidi
Abstract: BACKGROUND: Pesticides are extensively used worldwide to control plant pathogens and prevent agricultural product damage. However, they can pollute the environment and endanger human health. So far, a variety of sample preparation methods have been developed for the analysis of pesticide residues. RESULTS: A hyphenated solid–liquid microextraction method based on a new adsorbent of magnetic graphene oxide functionalized by (3‐glycidyloxypropyl)trimethoxysilane and a deep eutectic solvent (choline chloride/4‐chlorophenol (1:2)) was developed for extraction/preconcentration of trace levels of pesticides. The sorbent was characterized using scanning electron microscopy, Fourier transform infrared spectroscopy, and vibrating sample magnetometry. In‐syringe magnetic dispersive solid‐phase extraction in tandem with dispersive liquid–liquid microextraction followed by gas chromatography was applied for the analysis of the selected pesticides. The main parameters governing sample preparation efficiency, including adsorbent dosage, desorption conditions, pH, extraction time, deep eutectic solvent volume, and salt concentration, were investigated. The linear ranges were 0.024–500 μg L −1 with 0.9971–0.9999 linearity factor ( R 2 ). The limits of detection and quantification were 0.006–0.038 and 0.024–0.126 μg L −1, respectively. The relative standard deviations were 0.5–4.2% for intra‐day analysis and 2.7–4.6% for inter‐day analysis. Enrichment factors were in the range 210–540. CONCLUSIONS: The method was successfully applied for the determination of malathion, heptachlor epoxide, endrin, dichlorodiphenyltrichloroethane, azinphos ethyl, cypermethrin, and deltamethrin in fruit juice samples (apple, pineapple, cherry, peach, and red and green grape juices) and the recoveries were within the range 71–115%. © 2020 Society of Chemical Industry